Network and system security - Vacca, John R. (Syngress, 2014)
This book provides focused coverage of network and system security technologies. It explores practical solutions to a wide range of network and systems security issues. Coverage includes building a secure organization, cryptography, system intrusion, UNIX and Linux security, Internet security, intranet security, LAN security; wireless network security, cellular network security, RFID security, and more.